2019
DOI: 10.1121/1.5098950
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude modulation detection and modulation masking in school-age children and adults

Abstract: Two experiments were performed to better understand on- and off-frequency modulation masking in normal-hearing school-age children and adults. Experiment 1 estimated thresholds for detecting 16-, 64- or 256-Hz sinusoidal amplitude modulation (AM) imposed on a 4300-Hz pure tone. Thresholds tended to improve with age, with larger developmental effects for 64- and 256-Hz AM than 16-Hz AM. Detection of 16-Hz AM was also measured with a 1000-Hz off-frequency masker tone carrying 16-Hz AM. Off-frequency modulation m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 54 publications
1
3
0
Order By: Relevance
“…Evolution of AM detection and AM masking from 6 to 9 years of age and in children versus adults AM detection was tested with carriers with or without inherent random (competing) AM fluctuations (i.e., narrowband noises in the Noise condition, versus pure tones in the Tone condition). As expected based on previous studies (Hall and Grose, 1994;Banai et al, 2011;Peter et al, 2014;Buss et al, 2019;Cabrera et al, 2019), AMDTs were not overall adult-like by 9 years of age. We also observed that the thresholds did not significantly improve with age between 6 and 9 years.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…Evolution of AM detection and AM masking from 6 to 9 years of age and in children versus adults AM detection was tested with carriers with or without inherent random (competing) AM fluctuations (i.e., narrowband noises in the Noise condition, versus pure tones in the Tone condition). As expected based on previous studies (Hall and Grose, 1994;Banai et al, 2011;Peter et al, 2014;Buss et al, 2019;Cabrera et al, 2019), AMDTs were not overall adult-like by 9 years of age. We also observed that the thresholds did not significantly improve with age between 6 and 9 years.…”
Section: Discussionsupporting
confidence: 88%
“…In this connection, previous studies have shown differences in AM masking effects between young children versus adults. Specifically, Buss et al (2019) have observed higher susceptibility to AM masking in 5-year-olds than in adults for off-frequency conditions but not for on-frequency conditions, interpreted as the sign of ongoing maturation of selective listening. Cabrera et al (2019), in turn, found increasing susceptibility to AM masking between 5 and 7 years of age when comparing AM detection thresholds for deterministic vs non-deterministic carriers (pure tones vs narrowband noises respectively).…”
Section: Introductionmentioning
confidence: 80%
See 2 more Smart Citations